Supporting youth wellbeing with a focus on eating well and being active: views from an Aboriginal community deliberative forum. (14th February 2018) - Street, Jackie; Cox, Heather; Lopes, Edilene; Motlik, Jessie; Hanson, Lisa
Abstract: Objective: Including and prioritising community voice in policy development means policy is more likely to reflect community values and priorities. This project trialled and evaluated a storyboard approach in a deliberative community forum to engage Australian Aboriginal people in health policy priority setting. Methods: The forum was co‐constructed with two Aboriginal community‐controlled organisations. A circle storyboard was used to centre Aboriginal community knowledge and values and encourage the group to engage with broader perspectives and evidence. The forum asked a diverse (descriptively representative) group of Aboriginal people in a rural town what governments should do to support the wellbeing of children and youth, particularly to encourage them to eat well and be active. Results: The storyboard provided a tactile device to allow shared stories and identification of community issues. The group identified policies they believed governments should prioritise, including strategies to combat racism and provide local supports and outlets for young people. Conclusions: An informed deliberative storyboard approach offers a novel way of engaging with Aboriginal communities in a culturally appropriate and inclusive manner. Implications for public health: The identification of racism as a major issue of concern in preventing children from living healthy lifestyles highlights the need for policy responses in this area.